Thermal stability of a nanolayered metal joint. (15th March 2021) - Brunow, Jakob; Ritter, Martin; Krekeler, Tobias; Ramezani, Majid; Rutner, Marcus
Abstract: Recently, the first microstructure-preserving approach to metal joining of physical vapor-deposited nanolaminates was introduced. In a subsequent study, this metal lap joint is exposed to annealing cycles with target temperatures of 100°C, 200°C, 400°C and 800°C. The thinning-out ends (wedges) of the laminate and overlapping laminate of the lap joint provide challenges as well as new insights into thermal stability of nanolaminate. Energy dispersive x-ray spectroscopy mapping in the Scanning Transmission Electron Microscope (STEM) of the joint cross section proves that melting of the Cu-layers initiates at the tip of the wedges, where the laminate interface is as susceptible to melting as the lamina interface. A Melting Point Depression curve for the Cu/Nb nanolayered metal joint is established. The article further introduces the protective effect of covering laminate as the Shielding Effect and discusses the counteracting phenomena Melting Point Depression and Shielding Effect. Graphical abstract: Image, graphical abstract